ANTESEDEN DAN KONSEKUENSI KETERLIBATAN OTORITAS GEREJA DALAM SELEKSI PADA PENINGKATAN MOTIVASI BERPRESTASI DAN KINERJA GURU PAK PAPUA SELATAN - Donatius Wea S. Turu; Berlinda S. Yunarti (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2022)
The purpose of this study was to analyze the influence of the involvement of Church authorities in the selection of spiritual intelligence, achievement motivation and performance of Catholic religious education teachers. Primary data was obtained through questionnaires distributed to 70 Catholic religious education teachers spread across the Merauke archdiocese (which includes Merauke, Boven Digoel and Mappi regencies). There are five hypotheses that need to be tested using Structural Equation Model (SEM) analysis as a tool to see the relationship between variables using AMOS software. Measurement of variables using a Likert scale of 1 to 5, with a score of Disagree (Score 1) to Strongly Agree (score 4). The results of the study will show whether the five hypotheses are proven to have a positive and significant effect or vice versa. The results of this study are a very meaningful contribution to the Church Authority (local church leaders) and to Catholic religious education teachers.